EMPLOYEE TURNOVER WITHIN THE LABOUR RELATIONS PROGRAMME OF THE DEPARTMENT OF LABOUR - Ntsevu, Luvo (My University, 2012)
The employee turnover experienced within the Labour Relations Programme of the National Department of Labour was assumed to have an adverse effect on the service delivery. The aim of the study was to investigate the reasons for the high employee turnover within the Programme. The study followed a qualitative methodology, using semi-structured interview technique to collect data from a sample of ten participants. The participants consisted of current staff members and ex-staff members of the Programme. The study found that the most common reasons for voluntary employee turnover within the Programme were lack of growth and career opportunities, lack of career advancement and better opportunities, lack of challenging jobs, poor leadership and management style, recruitment and selection internal organisation politics. The study further found out that employees in the Programme stay because of personal and security reasons.
MM thesis - P&DM
Keywords: Employee turnover; Staff turnover; Personnel management